Much ado about nothing: An example of how failed incentives thwarted the implementation of the EU landing obligation. (January 2021) - Ovegård, Mikael; Sundelöf, Andreas; Valentinsson, Daniel
Abstract: With the introduction of the landing obligation in the EU common fisheries policy, there has been several initiatives to reduce unwanted catches of quota-regulated species. In this study, we present a flexible sorting grid as a potential solution for the problem of bycatch of saithe in the pelagic herring trawl fishery in the Skagerrak. The development of the grid was initiated by the industry and finalised through an industry-science collaboration project. The selectivity of the grid was evaluated through the use of an underwater camera system during conventional trawling with an industrial pelagic herring trawler. The results showed that the grid reduced the bycatch by more than 90%, from approximately 5% to 0.5% of the total catch. Given the scale of the pelagic fishery, this reduction could decrease unwanted bycatch of saithe by up to 1000 tonnes per year in the Skagerrak alone. These results were communicated to national industry and management representatives and to responsible EU management bodies and advisory councils. The work conducted within the project also drew interest at the yearly negotiations between EU and Norway. In their agreement for 2018, the EU and Norway agreed to establish a working group on technical measures in the Skagerrak tasked with reviewing selectivity of pelagic trawls as part of the terms of reference. However, in the agreed record of the delegations, the question of pelagic gear selectivity in the Skagerrak was a non-issue, although they concluded that the demersal bycatch can be substantial, that a sorting grid can reduce this bycatch and a sorting grid remains mandatory for Norwegian vessels in the Skagerrak. We argue that this result can be seen as a missed opportunity for the EU to reduce unaccounted bycatch in the Skagerrak and ensure better implementation of the landing obligation.